Analisis Faktor Yang Berhubungan Dengan Peran Perawat Sebagai Care Giver Dalam Penerapan Keselamatan Pasien Melalui Pendekatan Compliance Model Di IGD: Analysis - Wulandari, Dewi; Ixora, Ixora (Jurnal Keperawatan Terapan, 2025)
Nurses in carrying out their role as care givers have the task of caring for patients, making decisions, communicating and collaborating with other health teams. The Emergency Room is part of the hospital that provides initial treatment for patients. The implementation of patient safety carried out by nurses is a form of compliance in every action or interaction with patients in accordance with a compliance theory or known as the "Compliance Model" (Charles et al, 2003). The design in this study was analytical observation using a cross-sectional approach. This study was conducted in the Emergency Room of Dr. Soedomo Trenggalek Hospital in March - April 2019. The population in this study were all nurses in the Emergency Room of Dr. Soedomo Trenggalek Hospital as many as 30 people with the sample being nurses in the Emergency Room of Dr. Soedomo Trenggalek Hospital. The sampling procedure was carried out using total sampling. The researcher used an instrument in the form of a questionnaire. The factor that most influences the role of nurses as care givers in implementing patient safety through the compliance model approach in the Emergency Room is the nurse’s attitude. Hospitals are required to provide continuous education and training, periodic socialization of training results to improve the knowledge and skills of officers in implementing patient safety so that it has an impact on optimal nurse performance. Patient safety as a global issue must be included in the education curriculum and become a target for student competency achievement so that new nurses can implement patient safety.